2020
DOI: 10.1111/jphs.12347
|View full text |Cite
|
Sign up to set email alerts
|

Impact of community-based educational intervention on antibiotic use and resistance awareness among the people living in Ras Al Khaimah, United Arab Emirates

Abstract: Objectives Antibiotic resistance is a major global public health concern today. We explored the usefulness of an educational intervention in increasing antibiotic-related awareness of the public. Methods This community-based interventional study was conducted among 100 people living in Ras Al Khaimah, UAE. Preintervention awareness regarding antibiotics and antibiotic resistance was assessed using the World Health Organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Moreover, the present study finding was consistent with Rabbani et al, (2020) who assess the awareness of people living in United Arab Emirates regarding antibiotics and antibiotic resistance and reported that the intervention led to significant improvement in their knowledge of antibiotics and resistance.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the present study finding was consistent with Rabbani et al, (2020) who assess the awareness of people living in United Arab Emirates regarding antibiotics and antibiotic resistance and reported that the intervention led to significant improvement in their knowledge of antibiotics and resistance.…”
Section: Discussionsupporting
confidence: 91%
“…The misuse and improper disposal of medications are a major safety and environmental concern, and therefore, the proper disposal of these medications is critically important 16,17 . Research has revealed that medications are not properly handled in different patterns which were either: disposal in waste water, improperly used for self‐medication or used in overdose 18,19 . Such improper handling led to multiple high risk consequences such as prescription drug abuse, antibiotic resistance and death 20‐22 .…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Research has revealed that medications are not properly handled in different patterns which were either: disposal in waste water, improperly used for self-medication or used in overdose. 18,19 Such improper handling led to multiple high risk consequences such as prescription drug abuse, antibiotic resistance and death. [20][21][22] Children are the ones most affected and exposed to improper household drug waste.…”
mentioning
confidence: 99%
“…The reasons behind this unsafe disposal are lack of awareness of the proper method of disposal and risk associated with this unsafe disposal of antibiotics, absence of guidance of disposal of unused and expired antibiotics, absence of any surveillance system, educational interventions, and absence of any regulatory environmental laws for the disposal of antibiotics. Community‐based awareness programs for appropriate antibiotics use and proper disposal of expired/unused antibiotics was proved a great strategy to combat AMR (Rabbani et al., 2020).…”
Section: Resultsmentioning
confidence: 99%